2018
DOI: 10.1007/s11214-018-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Seismic Propagation and Coupling Through Mars’ Regolith: Implications for the InSight Mission

Abstract: NASA's InSight Mission will deploy two three-component seismometers on Mars in 2018. These short period and very broadband seismometers will be mounted on a threelegged levelling system, which will sit directly on the sandy regolith some 2-3 meters from the lander. Although the deployment will be covered by a wind and thermal shield, atmospheric noise is still expected to couple to the seismometers through the regolith. Seismic activity on Mars is expected to be significantly lower than on Earth, so a characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Less clear peaks occur around 10 Hz for the MPS measurements and 20 Hz for the Vulcano measurements. No indication of resonances between the LVL and the regolith at high frequencies that affect the vertical component only, as observed by Myhill et al (2018) during a field campaign in Iceland, are evident for the two cases in which measurements were conducted on sand. Spectral peaks observed on the vertical component are matched closely on the horizontal ones, as described above, and are also visible on the reference sensor.…”
Section: Lvl Effectsmentioning
confidence: 72%
See 2 more Smart Citations
“…Less clear peaks occur around 10 Hz for the MPS measurements and 20 Hz for the Vulcano measurements. No indication of resonances between the LVL and the regolith at high frequencies that affect the vertical component only, as observed by Myhill et al (2018) during a field campaign in Iceland, are evident for the two cases in which measurements were conducted on sand. Spectral peaks observed on the vertical component are matched closely on the horizontal ones, as described above, and are also visible on the reference sensor.…”
Section: Lvl Effectsmentioning
confidence: 72%
“…for all sensors around 2 Hz in the CNES case and, less clear, around 1.6 Hz for the measurement on Vulcano. These frequencies are smaller by an order of magnitude than predicted by Myhill et al (2018), and the exactly same effect is also observed on the reference sensors not mounted on the LVL, and, in case of the CNES measurements, not placed on sand, so it is hard to link the Fig. 14 Power density spectra for measurements to characterize the LVL effect.…”
Section: Lvl Effectsmentioning
confidence: 74%
See 1 more Smart Citation
“…However, at higher frequencies (>10 Hz), the lander-SEIS distance becomes comparable to the typical wavelengths of seismic propagations and the static deformation hypothesis may no longer be valid. Additionally, in real regolith, the behaviour is unlikely to be fully elastic and there will be some frequency dependant attenuation (Teanby et al 2016;Myhill et al 2018). As we have no frequency dependent attenuation in the elastic ground deformation model used, the amplitudes of the resonances in the observed seismic signal may be overestimated.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…According to Myhill et al (2018), the damping of the ground under the lander feet, D (in kg/s) for a given mass (m) can be expressed as:…”
Section: Ground Propertiesmentioning
confidence: 99%